Diagnosing X-pinch and cylindrical wire array Z-pinch with an all-optical framing camera on the "QiangGuang-I" facility. (22nd September 2022) - Song, Y.; Peng, B.D.; Song, G.Z.; Yue, Z.Q.; Duan, B.J.; Li, Y.; Cao, N.; Xu, Q.; Han, C.C.; Yao, Z.M.; Yan, W.P.; Ma, J.M.; et al.
Abstract: An all-optical framing camera has been established on the 1-MA "QiangGuang-I" facility for investigating the imploding dynamics of the X-pinch and the cylindrical wire array Z-pinch. This camera measures the photons flux distribution by detecting the photon-induced refractive index changes in the InP semiconductor with a probe laser beam. The InP-based imaging sensor with a 100 nm thick Al film and a 10 μm thick gold transmission grating of 20 μm spatial period was fabricated based on the lithography method. Two sequential frames with 1.5 ns time resolution and 13 ns inter frame separation time can be recorded in one single shot. Framing images indicating the plasma generation and dissipation of the X-pinch and the cylindrical wire array Z-pinch have been obtained, showing that this framing camera is a promising technique for investigating the mechanisms of the Z-pinch and other high energy density physics.